2005
DOI: 10.1002/chem.200500516
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Gated Synthetic Ion Channels

Abstract: Supramolecular pi-stack architecture is fundamental in DNA chemistry but absent in biological and synthetic ion channels and pores. Here, a novel rigid-rod pi-stack architecture is introduced to create synthetic ion channels with characteristics that are at the forefront of rational design, that is, ligand gating by a conformational change of the functional supramolecule. Namely, the intercalation of electron-rich aromatics is designed to untwist inactive electron-poor helical pi-stacks without internal space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 52 publications
4
81
0
Order By: Relevance
“…To summarize, the anion/cation selectivity of ion channels 3 and 4 obtained from the HPTS assay was identical with that obtained in BLMs. [7][8][9][10] The selectivity sequence of anion channel 4 obtained from the HPTS assay was partially identical with that obtained in The anion/cation selectivity of pore 6 obtained by comparison of CF and ANTS/DPX assay was identical with that obtained in BLMs. 13,15 The same was true for the deletion of the cation selectivity of pore 6 with Mg 2þ .…”
Section: Correlation Of Results On Ion Selectivity From Blms and Luvssupporting
confidence: 71%
See 2 more Smart Citations
“…To summarize, the anion/cation selectivity of ion channels 3 and 4 obtained from the HPTS assay was identical with that obtained in BLMs. [7][8][9][10] The selectivity sequence of anion channel 4 obtained from the HPTS assay was partially identical with that obtained in The anion/cation selectivity of pore 6 obtained by comparison of CF and ANTS/DPX assay was identical with that obtained in BLMs. 13,15 The same was true for the deletion of the cation selectivity of pore 6 with Mg 2þ .…”
Section: Correlation Of Results On Ion Selectivity From Blms and Luvssupporting
confidence: 71%
“…8 The cationic interior of ion channel 4 was as well reflected in P Cl À =P K þ ¼ 3:0 as the anionic interior of pore…”
Section: Planar Bilayer Conductance Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amides were added at both sides of the NDI to orient the π-stacks with H-bonded chains [45,46]. Denaturation-corrected Hill analysis demonstrated self-assembly into tetrameric architecture as expected for π-helix 12 [42].…”
mentioning
confidence: 89%
“…Functional and structural studies revealed that the helix-barrel transition from photosystem 12B to ion channel 19 is highly cooperative, sensitive, and selective with regard to ligand and channel structure. Ion channels 19 are small, anion-selective, ohmic, and remarkably homogenous considering the complexity of the architecture [46]. In summary, it is possible to synthesize supramolecular architectures that can function as ion channels, pores, or photosystems.…”
mentioning
confidence: 99%